Hepatocelular Carcinoma Misdiagnosed as Focal Nodular Hyperplasia. Case Report - Rosyidi, Muhammad Yunus; Tripriyanggara, Ardhi (Journal of Neonatal Surgery, 2025)
Introduction: Focal Nodular Hyperplasia (FNH) often mimics Hepatocellular Carcinoma (HCC) in imaging, making biopsy essential to confirm the correct diagnosis. A clear understanding of FNH's features is necessary to avoid misdiagnosis and improper treatment. Case Report: A 29-year-old woman experienced lumps and pain in the upper abdomen. Her lab results showed an AFP level of 76 ng/mL. The CT scan revealed a solid mass with central scarring in the left liver lobe, measuring approximately 3.9 x 4.7 x 3.5 cm, consistent with FNH. The core biopsy indicated liver tissue with cholestasis and no malignancy. However, following resection of the left liver lobe, pathology confirmed hepatocellular carcinoma (HCC). Discussion: The CT scan showed a solid mass characteristic of FNH, and the core biopsy also supported FNH. However, post-resection pathology revealed HCC. This difference was due to the smaller tissue sample obtained through core biopsy, as open biopsy provides a more comprehensive sample, allowing for a more accurate assessment of malignancy, a clearer diagnosis, and better guidance for treatment. Conclusion: Understanding the characteristics of FNH is essential from CT Scan, and biopsy should be considered the gold standard for accurate diagnosis. Open biopsy, with its larger tissue sample, can improve diagnostic precision